Accuracy of 1RM Prediction Equations Before and After Resistance Training in Three Different Lifts - Alex Ribeiro; Jefferson Alencar da Silva; Matheus Nascimento; Diogo Martinho; Leandro dos Santos; Belmiro de Salles; Jerry Mayhew; Edilson Serpeloni Cyrino (International Universities Strength and Conditioning Association, 2024)
This study aimed to assess the accuracy of one repetition maximum (1RM) prediction equations for three resistance exercises in young men and women before and after a resistance training program. Sixty-two women (21.6±3.7 years, 58.5±12.2 kg, and 162.4±6.2 cm) and 57 men (22.8±3.8 years, 70.5±9.3 kg, and 177.0±6.4 cm) performed 16 weeks of a progressive and supervised resistance training. Before and after the 16-week program, the participants performed a 1RM and an endurance test consisting of one set at 80% until muscular failure. The tested exercises were bench press (BP), squat (SQ), and arm curl (AC). The load and number of repetitions performed in each exercise were used to predict the 1RM using nine equations. This design enabled verification of the accuracy of each equation to estimate 1RM scores in young men and women before and after a 16-week RT program. For men, the Lombardi equation was the most accurate for predicting 1RM in BP and SQ, presenting similar results to actual the 1RM before and after RT. All equations presented significant differences for AC before and after training. For women, the Brown, Brzyski, and Lander equations produced similar 1RM scores to the actual values for BP and SQ. For AC, Mayhew, Wathen, and Welday equations produced similar scores to actual 1RM before and after training. Results suggest that using some selected prediction equations to estimate 1RM before and after a resistance training period is a valid method for young men and women in different lifts.